Laparoscopic Total Gastrectomy for Gastric Cancer in Elderly Patients - SUEMATSU, HIDEAKI (In Vivo, 2020)
Background/Aim: The purpose of this study was to evaluate the safety and efficacy of laparoscopic total gastrectomy (LTG) for elderly patients. Patients and Methods: We retrospectively analyzed 136 patients who underwent LTG. We divided the patients into elderly patients (>75 years of age) and non-elderly patients (≤75 years of age). Results: The American Society of Anesthesiologists score, Charlson comorbidity index, Glasgow Prognostic Score and rate of comorbidities were higher in the elderly group; the rates of other clinicopathological characteristics did not differ between the two groups. Regarding the nutritional status, the body weight loss rate in the elderly group was higher in comparison to the non-elderly group (81% vs. 84%, p=0.004). The disease-specific survival (DSS) did not differ between two groups to a statistically significant extent (3-year DSS rates: 83.7 vs. 94.5%; p=0.152). Conclusions: LTG was acceptable for elderly patients as the elderly and non-elderly groups showed comparable short-term and long-term outcomes.